A General Strategy for Engineering Robust Core-Shell Surface-Enhanced Raman Scattering Interfaces of Metal-Organic Framework@Plasmonic Nanoparticles - Sun, Peng (Langmuir : the ACS journal of surfaces and colloids, 2025)
The unique physicochemical properties of core-shell interface structures make them attractive for technological applications in sensing, catalysis, and hydrogen storage. In this work, we present a general strategy based on mussel-inspired polydopamine (PDA) chemistry to engineer a robust surface-enhanced Raman scattering (SERS) interface in core-shell metal-organic frameworkplasmonic nanoparticles (MOF@PNPs). The ability of PDA to adhere to host materials of any chemical composition and to induce localized reduction of metal precursors made it robust for the integration of diverse MOFs and PNPs. The PDA-based method allowed for the deposition of common PNPs on the three classical MOFs with controlled plasmon properties, leading to the formation of core-shell MOF@PNPs with SERS-active interfaces. The simulation results revealed that the heterostructures provided a hot spot field larger than that of the standard aggregated PNPs. With a Raman internal standard of MOFs, the representative substrates have been successfully applied to the quantitative and sensitive detection of nerve agent simulation. Such core-shell interfaces are of great potential for SERS applications and may provide new insights into the mechanism of SERS